Molecular epidemiology and antimicrobial susceptibility of Pseudomonas spp. and Acinetobacter spp. from clinical samples at Jimma medical center, Ethiopia - Sewunet, Tsegaye; Asrat, Daniel; Woldeamanuel, Yimtubezinash; Aseffa, Abraham; Giske, Christian G. (Frontiers in Microbiology, 2022)
Introduction Pseudomonas aeruginosa (P. aeruginosa) and Acinetobacter baumannii (A. baumannii) can cause difficult-to-treat infections. We characterized molecular epidemiology of ceftazidime-resistant P. aeruginosa and carbapenem-resistant A. baumannii at a tertiary hospital in Ethiopia. Materials and methods Non-fermenting gram-negative bacilli (n = 80) isolated from admitted patients were subjected for species identification by MALDI-TOF. Pseudomonas species resistant to ceftazidime or meropenem, and Acinetobacter species resistant to meropenem, or imipenem were selected for whole genome sequencing. DNA extracted with EZ1 Advanced XL instrument (Qiagen, Hilden, Germany) was sequenced on Illumina (HiSeq2500) using libraries prepared by NEXTRA-kits (Illumina). Raw reads were assembled using SPAdes 3.13.0, and assembled genomes were used to query databases for resistome profile and sequence types. Result Among Pseudomonas species isolated, 31.7% (13/41), and 7.3% (3/41) were non-susceptible to ceftazidime, and meropenem, respectively. Carbapenem-resistance was 56.4% (22/39) among Acinetobacter species. Moreover, 92% (12/13) of Pseudomonas species non-susceptible to ceftazidime and/or meropenem, and 89.4% (17/19) of Acinetobacter species encoded multiple resistance genes for at least three classes of antimicrobials. The prevalent β - lactamase genes were blaOXA–486 (53.8%, 7/13), blaCTX–M–15 (23.0%, 3/13) among Pseudomonas, and blaGES–11 (57.8%, 11/19) among Acinetobacter. The blaOXA–51-like β - lactamase, blaOXA–69 (63.1%, 12/19) was the most prevalent carbapenemase gene among Acinetobacter isolates. Single isolates from both P. aeruginosa, and A. baumannii were detected with the blaNDM–1. Sequence type (ST)1 A. baumannii and ST274 P. aeruginosa were the prevalent sequence types. A cgMLST analysis of the ST1 A. baumannii isolates showed that they were closely related and belonged to the international clonal complex one (ICC1). Similarly, ST274 P. aeruginosa isolates were clonally related. Conclusion The prevalence of MDR isolates of Pseudomonas and Acinetobacter spp. was high. A. baumannii isolates were clonally spreading in the admission wards at the hospital. Emergence of blaNDM–1 in the intensive care, and surgical wards of the hospital is a severe threat that requires urgent intervention.